"A Journey for Peace": Spatial Metaphors in Nixon's 1972 "Opening to China". Issue 4 (30th April 2017) - Carney, Zoë Hess; Prasch, Allison M.
Abstract : Richard Nixon's1972 "opening to China" is regarded as one of the most significant moments of U.S. foreign policy during the Cold War. Through his rhetoric before, during, and after his visit to the People's Republic of China, the president moved from established metaphors of communist nations and peoples as "savage enemies" and descriptions of "Red China" as a nation "lost" to communism to a narrative that suggested openness and friendship. In this essay, we argue that Nixon's use of spatial, territorial, and orientational metaphors such as "journey for peace, " "open the door, " "bridge, " "wall, " "common ground, " and "close the gulf, " compounded with his physical presence in China, are key for understanding the force of his rhetoric during this shift in U.S. Cold War foreign policy. In discursively and politically opening transnational U.S.–China relations, Nixon weakened the polarized East–West ideological and geographic divide and provided a new vision of Cold War geopolitics.